DEMONSTRATION OF PROCESSING AND BENEFITS OF JACKFRUIT SEED FOR PREGNANT WOMAN’S ADDITIONAL FOOD TO PREVENT STUNTING IN THE FIRST 1000 DAYS OF LIFE - Ramadhaniah Ramadhaniah; Fahrisal Akbar (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
One of the health problems that need to be watched out for in Indonesia is stunting in children under five. Stunting is a toddler whose height for ages is under -2 Standard Deviation from the WHO median standard (TB/U -2 SD) (WHO, 2012). Jackfruit seeds can be used in food development to increase the nutritional content of food products which can be used to address nutritional problems, one of which is stunting. Making biscuits with the addition of jackfruit seeds is expected to have a high nutritional content so that they can be an alternative nutritional snack for stunting toddlers (WHO, 2012). The purpose of the service is to overcome the nutritional problems of stunting cases in toddlers in the PODIHAGU area and introduce local food ingredients with many health benefits. The implementation method is carried out face-to-face (offline) with the lecture method at the house of a resident in Podihagu Hamlet. Conclusion to increase public knowledge about the benefits of jackfruit seeds for toddler health. The importance of increasing public knowledge of the importance of the problem of malnutrition in toddlers or cases of stunting health. The importance of public knowledge about the benefits of leaves and flour from jackfruit seeds for various health treatments.Keywords: Stunting; jackfruit seeds; Jackfruit Seed Flour